Penerapan Proteksi Radiasi Di Instalasi Radiologi Rumah Sakit RSKD Dadi Provinsi Sulawesi Selatan - Sitti Normawati (Pusat riset dan Inovasi Nasional, 2022)
Radiation protection is a branch of science and engineering that discusses environmental health which is related to providing protection to a person or group of people from the possible negative consequences of ionizing radiation. This research aims to determine the implementation of radiation protection in the Radiology Installation at Dadi Hospital, South Sulawesi Province. This study uses research methods, namely conducting observations and interviews at the hospital. Based on the research results, it was concluded that the implementation of radiation protection in the Radiology Installation room at Dadi Hospital, South Sulawesi province was not in accordance with Bapeten's operational standards so its implementation was not optimal.